Binding stability of β-CD on MWCNTS: Role of washing cycle on the β-CD coating - Jawad, Z.A. (Penerbit Universiti Sains Malaysia, 2017)
The functionalisation of carbon nanotubes (CNTs) represents a strategy not only to improve the CNTs dispersion, solubility, and processability, but also to allow strong interfacial interactions to take place between CNTs and guest molecules. In this study, beta-cyclodextrins (β-CD) was used to functionalise the sidewalls of multi-walled CNTs (MWCNTs) for better stability. The role of washing cycles on the β-CD binding was investigated. The results indicated that the mean diameter of MWCNTs was retained at almost the same size even after three cycles of washing. This observation confirmed the strong binding between MWCNTs and β-CD. © Penerbit Universiti Sains Malaysia, 2017.